2007
DOI: 10.1117/12.711177
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive pulses and laser-induced retinal injury thresholds

Abstract: Experimental studies with repetitively pulsed lasers show that the ED 50 , expressed as energy per pulse, varies as the inverse fourth power of the number of pulses in the exposure, relatively independently of the wavelength, pulse duration, or pulse repetition frequency of the laser. Models based on a thermal damage mechanism cannot readily explain this result. Menendez et al. proposed a probability-summation model for predicting the threshold for a train of pulses based on the probit statistics for a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…2, where the MP reduction based on a slope of one is much greater than the reduction based on a slope of 20. Lund 5,7 has shown that the PSM can be used to derive the n −1∕4 trend that has been repeatedly observed. The PSM predicts (after a few approximations) that the MP ED 50 trend should be n −1∕β , where β is the SP dose-response slope minus 1 (β ¼ SL − 1).…”
Section: Probit Slope For Small-spot In-vivo Datamentioning
confidence: 99%
See 1 more Smart Citation
“…2, where the MP reduction based on a slope of one is much greater than the reduction based on a slope of 20. Lund 5,7 has shown that the PSM can be used to derive the n −1∕4 trend that has been repeatedly observed. The PSM predicts (after a few approximations) that the MP ED 50 trend should be n −1∕β , where β is the SP dose-response slope minus 1 (β ¼ SL − 1).…”
Section: Probit Slope For Small-spot In-vivo Datamentioning
confidence: 99%
“…The idea is that one can compare actual damage threshold trends for MP exposures to the predictions of the PSM to identify interaction effects between pulses and even determine if a positive (sensitizing) or negative (desensitizing) effect exists. Lund 5 has suggested that the discovery of the microcavitation damage mechanism has provided a physical justification for the statistical independence assumption made by the PSM. The probability of damage occurring is just the probability of a microcavitation event occurring and therefore does not depend on the thermal addition between pulses.…”
Section: Modelmentioning
confidence: 99%